The Political Economy of the G20 Agenda on Financial Regulation - Ludger Schuknecht; Vincent Siegerink (Center for Economic Studies and Ifo Institute (CESifo), 2020)
The paper empirically examines the implementation record of international financial regulation of the banking sector. The study finds that the size of the banking sector and the presence of global systemically important banks (G-SIBs) are positively associated with a stronger implementation record. These results suggest that cooperative motives of internalising externalities, creating a level playing field and preserving financial stability play a role in explaining the implementation record. We find evidence that this cooperative behaviour may be driven by the self-interest of global players as the positive record is particularly strong in countries where large banking sectors and big banks are both present, and where regulation only applies to large players. Sectoral concentration, bank health and the share of foreign ownership yield more mixed results as regards their impact on implementation.
Keywords: D70; F55; G15; H26; 330; policy coordination; international public goods; financial regulation; rent seeking